Information technology application of nuclear power station commissioning under the background of internet+ - Youwen FANG; Fuquan ZHANG; Liang YE (Dianxin kexue)
Early in the process as the center of nuclear power engineering information has some limits, such as old architecture, extensibility, poor user experience, insufficient workflow engine, unstandard data, complex interface, etc. In order to solve these problems, combined with existing achievements of intelligent power station project of company, idea of promoting informatization construction step by step from four aspects of foundation platform construction, standardization construction, fine management, innovation application, was put forward. Based on top level design scheme of intelligent power station project of company, the detailed construction plan was elaborated from the aspects of architecture, application scenarios and data assets. Finally, advice was given on the informatization implementation path, operation mechanism and demonstration construction project.